Wrestling coaches' overcoming needs for talent selection through dermatoglyphs (Original) (Revista científica Olimpia, 2021)
This work shows a study of the need for improvement of school wrestling coaches in the province of Camagüey, on the use of the dermatoglyph method as a genetic indicator for the prediction of future sports talents, which contributes to enriching the sports selection process. For which, the professional performance test is applied as a validated instrument in Advanced Education, whose results in the cognitive, instrumental and attitudinal dimensions confirmed the need to design ways of overcoming aimed at equipping the school struggle coaches with a new method. that complements the selection process for sports talent.
Keywords: dermatoglyphs; professional improvement; talent selection